Adaptability of Intercultural Communication of Immigrants as Traditional Administrators in Local Communities - Radiyus, Radiyus (Eduvest - Journal of Universal Studies, 2025)
This research is entitled "Adaptability of Intercultural Communication of Immigrants as Traditional Administrators in Local Communities (Ethnographic Study of Minangkabau and Javanese People in Ethnic Management in Mukomuko Regency)". The purpose of this study is to explore how migrants can adapt to local culture in Mukomuko Regency, especially in the context of customary management. In a multicultural society like Mukomuko, intercultural communication is the key to building harmonious social relationships. This study analyzes the factors that affect the adaptation process, including language differences, values, and cultural norms. This adaptation process includes several phases, ranging from the honeymoon phase, frustration, readjustment, to resolution. The study also notes that despite the challenges, migrants who interact with local communities demonstrate the ability to align themselves with traditions and indigenous values. Through qualitative approaches and ethnographic methods, data were collected through in-depth interviews and observations. The results of the study show that migrants who actively communicate and interact with the local community can obtain a position as a traditional administrator, which was previously considered taboo. This research contributes to understanding the dynamics of intercultural communication and the importance of adaptation in diverse social contexts, as well as providing insights for local communities and immigrants in building better relationships.